7 - Cultural Modes of Comprehending and Healing Insanity: The Yaka of DR Congo: DOI: 10.4314/ad.v30i3.22232 - Devisch René (Africa Development, 2005)
This paper looks at a particular autochthonous medical knowledge and practice of Yaka healers in peri-urban Kinshasa and rural southwestern Congo. It first presents a sequential analysis of the well-known mbwoolu healing cult, directed at types of affliction most of which I would characterize as deep depression and related insanity. The mbwoolu patient is first led into a state of fusion with the group, with the aid of rhythmic movement and music culminating in a trance possession. Following this, the initiate undergoes a therapeutic seclusion lasting from one month to some nine months in an initiatory space in which a dozen or so statuettes or figurines are laid on a bed parallel to the patient's. In a play of mirrors between the figurines and the patient, the latter's sensory perceptions and body movements are redirected and rejuvenated. The figurines thus function as doubles that the patient incorporates or inscribes in his or her own bodily envelope, which now constitutes a new interface with others. In the course of a verbal liturgy that unfolds to the rhythm of the initiatory rite, the initiate is gradually enabled to decode and incorporate traces of the collective imaginary conveyed by these figurines and liturgy. The statuettes enact a cosmogony in which the patient is intimately involved throughout. In this, the patient is led into an ontogenetic passage from a fusional and primal state towards a particular and sexualised identity, one with precise contours and situated within a social hierarchy and a historicity of generations and of roles.